2016
DOI: 10.1097/mjt.0000000000000034
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Hyperemesis Syndrome

Abstract: Cannabinoid hyperemesis is a relatively rare but significant adverse effect of chronic marijuana use characterized by severe, cyclic nausea, vomiting, and abdominal pain and marked by compulsive hot-water bathing for temporary symptom relief. A 37-year-old African American male with no significant medical history other than the habitual abuse of marijuana was admitted for intractable nausea, vomiting, and abdominal pain. With the exception of abdominal skin hyperpigmentation and scarring secondary to the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[32][33][34] Metoclopramide, ondansetron, and benzodiazepines have also been reported as effective in noncomparative studies. 18,[35][36][37] A recent retrospective cohort study compared the use of droperidol with other antiemetics for patients presenting with CHS to an ED and found shorter median lengths of stay and less ondansetron use in patients who received droperidol compared with those who did not. 38 For long-term therapy, one prospective study suggests that tricyclic antidepressants may represent a potentially beneficial option in CVS, although this was not specific to cannabinoid users.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
“…[32][33][34] Metoclopramide, ondansetron, and benzodiazepines have also been reported as effective in noncomparative studies. 18,[35][36][37] A recent retrospective cohort study compared the use of droperidol with other antiemetics for patients presenting with CHS to an ED and found shorter median lengths of stay and less ondansetron use in patients who received droperidol compared with those who did not. 38 For long-term therapy, one prospective study suggests that tricyclic antidepressants may represent a potentially beneficial option in CVS, although this was not specific to cannabinoid users.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
“…A case report of a 37-year-old African American male who is suffering from intermittent symptoms like nausea, vomiting and epigastric pain for the last 14 years has a history of long-term use of Cannabis and to relieve the symptoms the patient applies heat to the abdomen [191]. It remains a puzzle how CBs induce hyperemesis despite its antiemetic property demonstrated in clinical and animal models, by stimulating CB1 receptors [192].…”
Section: Cannabinoid Hyperemesis Syndromementioning
confidence: 99%
“…Abdominal heat application with hot showers helps in the redistribution of heat around the gastrointestinal tract and relieves the symptoms of CHS [194]. One case report suggests that chronic use of CBs may turn CHS into Cyclic Vomiting Syndrome (CVS) [191]. A study conducted by Simonetto and colleagues on 98 patients concluded that CHS symptoms occur in patients who use Cannabis frequently for many years and start to decline after the cessation of the Cannabis use [195].…”
Section: Cannabinoid Hyperemesis Syndromementioning
confidence: 99%
“…Interaction between Δ9-THC and CB1 receptors at low doses mediates as a partial agonist, creating antiemetic effects, although at high doses it may create hyperemesis (Darmani, 2002;Woods, Wright, Gee & Scobey, 2016). 2.…”
Section: Chs Etiologymentioning
confidence: 99%
“…2. Genetic vulnerability and high doses of cannabis mediate an alteration of the hepatic cytochrome p450 in the metabolization of Δ9-THC, increasing the concentration of the substance in the body (Woods et al, 2016). 3.…”
Section: Chs Etiologymentioning
confidence: 99%